Development of a local warfarin dosage guideline based on pharmacogenomics and haemostatic markers - An, Chua Yung (2016)
Warfarin, the mainstream oral anticoagulant, has a narrow therapeutic index and wide interindividual dose variability, rendering maintaining its optimal dose in each individual a difficult task. Many warfarin dosing models have been developed worldwide in order to improve the accuracy of currently used international normalised ratio (INR) dosing method. However, those dosing models were not practical to be used due to extensive additional data that are required for dose calculation. In this study, a simpler warfarin's dosing model for local population has been studied for warfarin therapy reinitiation based on clinical, laboratory and genetic data. A total of 130 of patients on warfarin treatment in Hospital Universiti Sains Malaysia were recruited for the model-building. Patients' clinical data were extracted from the hospital database. Polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) methods were used for genotyping of CYP2C9*2, *3 and VKORC1 -1639G>A while a newly developed nested allele-specific multiplex PCR was used for genotyping of VKORC1 381, 861, 5808 and 9041. Genotype data of VKORC1 381, 861, 5808 and 9041 were used to infer VKORC1 haplotype. The activity of vitamin K-dependent (VKD) clotting factors II, VII, IX and X were measured by using a benchtop haemostatic analyser. A newly developed and validated high performance liquid chromatography (HPLC) method with UV detector was used for measurement of serum warfarin levels that were subsequently used for pharmacokinetics data calculation in 24 patients. The warfarin's dosing model was developed by using a forward multiple linear regression. The heterozygous mutant genotype of CYP2C9*2 and *3 were rare (both at 3.8%), while the homozygous mutant was not detected. The frequency of VKORC1 -1639G>A andVKORC1 381 were similar. The genotype with highest frequency was the low warfarin's dose requirement genotype (GG: 54.6%). The VKORC1 H1H1, H1H7 or H1H9 and H7H7 were the most common haplotype pairs (53.1, 32.5 and 10.0%). All VKD clotting factor activities were not significantly associated with warfarin's dose requirement or with the INR. Maximum serum concentration, half-life and clearance of warfarin were not significantly associated with any genetic data or warfarin's dose requirement. The final warfarin's dosing model consists of age, the number of VKORC1 381 allele, mean INR and history of mitral valve replacement as useful predictor factors. The predictor factors explained 45.6% of warfarin dose variability. The developed dosing model is suitable to be used as guideline to determine the warfarin dose of patients who need to reinitiate a warfarin therapy.